2005
DOI: 10.1007/s11240-005-0883-9
|View full text |Cite
|
Sign up to set email alerts
|

Shoot regeneration, re-flowering and post flowering survival in bamboo inflorescence culture

Abstract: In vitro grown inflorescences of Bambusa edulis were used to investigate the process of vegetative shoot growth in detail. The findings revealed that auxins and ACC could be significant growth regulators in this process. Overall, auxins [NAA, indolebutyric acid (IBA), and 2,4-dichlorophenoxyacetic acid (2,4-D D )] induced inflorescences to grow vegetative shoots. However, the efficiency of shoot regeneration varied. A greater percentage (27.3-34.5%) of inflorescences in the 5 mg l )l NAA, 10 mg l )l NAA, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…BA has been reported to be effective in floral induction of a number of plant species, such as orchids (Chang and Chang. 2003;Naor et al 2004), bitter melon (Wang et al 2001), and bamboo (Lin et al 2005b). In this study, the influence of BA on in vitro flowering of D. zingiberensis was remarkable.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…BA has been reported to be effective in floral induction of a number of plant species, such as orchids (Chang and Chang. 2003;Naor et al 2004), bitter melon (Wang et al 2001), and bamboo (Lin et al 2005b). In this study, the influence of BA on in vitro flowering of D. zingiberensis was remarkable.…”
Section: Discussionmentioning
confidence: 57%
“…Floral induction was obtained via somatic embryogenesis and organogenesis in bamboo (Lin et al 2003(Lin et al , 2004(Lin et al , 2005b and Panax ginseng (Tang 2000). The combination of BA and GA 3 induced direct in vitro flowering in ginseng (Lin et al 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…1d & e). The role of IBA and NAA in root induction had been reported earlier in other bamboos like Bambusa vulgaris by [11]; in B. oldhamii by [12] and Dendrocalamus asper by [13]. Complete plantlets were hardened on soil: sand: farmyard manure (1:1:1) by gradually lowering the relative humidity and were successfully transferred from in vitro to natural environmental conditions with 80% survival rate.…”
Section: Rooting and Acclimatizationmentioning
confidence: 60%
“…When using in vitro inflorescences as explants, auxin-only medium increased the floret size, and also induced adventitious roots and caused 35% more vegetative shoots to emerge. These rooted vegetative plantlets could be transplanted to the greenhouse and survive (Lin et al, 2005). These results indicated that auxin plays a negative role in bamboo flowering and inflorescence proliferation in vitro .…”
Section: Flower Induction In Vitro: Control By Plant Growth Regulatorsmentioning
confidence: 99%
“…While only self-crosses have thus far successfully produced seeds in vitro (Nadgauda et al, 1990), advances in technology, new induction protocols, or alternative hybridization strategies can further the realization of this goal. For example, D. latiflorus and B. edulis plantlets induced to flower in vitro were successfully transferred to the greenhouse, where they continued flowering (Zhang and Wang, 2001; Lin C. C. et al, 2003; Lin et al, 2005). Perhaps parental bamboo accessions could be induced to flower in vitro and transplanted to the greenhouse for further hybridization with other bamboos that are flowering, whether they were induced in vitro or in vivo .…”
Section: Moving Forwardmentioning
confidence: 99%